Novel design and fabrication of MIM capacitors with alternating connection fingers - Seah, Yong Meng. (2013)
In this dissertation project, a series of novel MIM capacitors are designed. A novel process, compatible with GaAs MMICs is developed as well which allows the integration of passive devices and HEMT devices. Detailed description of the full design layout and fabrication process is presented in this report. The project demonstrated the successful fabrication of the novel MIM capacitors with an elongated structure. The design is elongated in shape to balance out on the effective capacitance area of the metal plates. The capacitors are typically designed by using alternating connecting fingers to link two closely spaced elongated capacitors. The connections target to make use of the parasitic capacitance to supplement to the overall capacitance value. Subsequently, a series of newly designed MIM capacitors are compared, together with the traditional square MIM capacitors. The coupling effects are studied from the design variations in some of the design parameters in this report. The relationship of these parameters with the overall capacitance value and self-resonant frequency of the novel MIM capacitors are also discussed and presented.